Study of Open and Sealed Auctions in Astra Credit Companies Using Batna and Zopa - Turipanam Alamanda, Dini; Ovinia Saraswati, Puspa; Sidiq Adi Prabowo, Fajar; Azhari, Muhammad (International Journal of Engineering and Technology, 2018)
Decision made by the finance companies in solving the bad credit problems is through the withdrawal of vehicles that have been financed, then sell them through the auction system. Truck withdrawal unit is the one with the highest auction frequency. The higher the auction frequency, the lower the vehicleâ€™s minimum price will become or the price will drop. The purposes of this study are to determine the best alternative to be carried out by Astra Credit Companies when analyzed using BATNA in open ascending and sealed highest bid auctions, and to know the price range and condition class of the auction unit that allows for an agreement to take place when analyzed using ZOPA. Based on the type, this is a descriptive qualitative research involving longitudinal observations. The data was collected through interviews with the representatives of Astra Credit Companies and the bidders, observations of the auction processes, and analyses of the auction resultâ€™s documentations study. The results reveal that open auction generates higher sales than the sealed one, but the biggest margin between the minimum price and the selling price takes place in the sealed auction. The amount of the minimum price depends on the condition class and the frequency of the auction events of each unit. The suggestion that can be implemented based on the research results for the companies is that they should provide information on an ongoing basis for the prospective bidders or partnering dealers to increase their participations. The maximum payment is results from the sales of ISUZU NKR71HD WOODEN TRUCK (sealed auction) and NKR71 HDDUMPTRK (open auction).Â Â